Faktor Yang Mempengaruhi Kinerja Karyawan (Studi Kasus KSO Pertamina EP–Gunung Kampung Minyak.Ltd) - Anggreany Hustia; Fitantina Fitantina; Nadia Afrilliana (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Some theories say there are many things that affect employee performance in a company including employee satisfaction, employee environment and compensation given to employees. The existence of this study was conducted to find out whether these factors actually impacted or affected the performance of the employees of the KSO Pertamina EP – Gunung Kampung Minyak case study. Ltd. The studied population of 69 employees and sampled only 59 employees, was conducted used primary data through the dissemination of questionnaires that contained indications of the factors studied. The picture of the resulted of this studied was to state that there was an influenced on job satisfaction and the worked environment on employee performanced. While the compensation factor was declared to had no effect on performanced. While for the resulted simultaneously obtained that the three factors studied in this studied had a confectioner over employee performanced.